Pengembangan Sistem Informasi Berbasis Web Untuk Pt. Xyz - Fictor Benny dan Rina Adi Kristianti (Universitas Tarumanagara, 2019)
This Journal discusses about the function of Information System useful for the company in facing the problems associated with the relationship between the company with the customer causing the number of miss communication so that affects all divisions and also relationships with customers. Customers in this journal is a distributor that can be said as customer level one or supplier of goods. In the journal problems obtained by approaching fish bone. What is then known that in need is an application that can be a liaison in both of these things.